Implementation of an Arabic spell checker - Rafik Kassmi; Samir Mbarki; Abdelaziz Mouloudi (Institute of Advanced Engineering and Science, 2024)
This paper outlines the implementation of a spell checker for the Arabic language, leveraging the capabilities of NooJ and its functionality, specifically noojapply. In this paper, we shall proceed to provide clear definitions and comprehensive descriptions of several categories of spelling errors. Next, we will provide a comprehensive introduction to the NooJ platform and its command-line utility, noojapply. In the subsequent section, we shall outline the four main phases of our spell checker prototype. We intend to develop a local grammar in NooJ for the purpose of error detection. Afterwards, a morphological grammar and a local grammar will be created in NooJ with the aim of providing an exhaustive list of possible corrections. Following that, a revised algorithm will be employed to arrange these candidates in descending order of ranking. Subsequently, a web user interface will be developed to visually represent our research efforts. Finally, we will proceed to showcase a series of tests and evaluations conducted on our prototype, Al Mudaqiq.